FORMATION OF STUDENTS 'READINESS FOR CREATIVE ACTIVITIES AS A FACTOR OF PERSONALITY DEVELOPMENT IN CONDUCTING TRAINING PROCESSES - O.H. Dolgova (Academy of Cognitive and Natural Sciences, 2007)
The article deals with the problem of actuality in demanol formation of personality self-realization, notional knowledge in philosophical and psychological and pedagogical literature is made up.